Determining Optimal Locations for Viewpoints Using the Open-Source Whitebox GAT Software (Geography and Tourism, 2019)
The most visually exposed landscape can be determined by a rich set of GIS tools, the main limitation of which is high intensity of computation. This study aims to put forward a method of specifying optimal location for the viewpoints attractive to tourists by means of Whitebox GAT, an open-source GIS application. The study area involves the Kolbudzko-Przywidzka Upland of the southern part of the Kashubian Lakeland in Poland. The method presented herein is characterized by simplicity and low computation intensity. However, it can only be used to analyse views on a local scale, in areas whose spatial coverage does not exceed a dozen or so kilometres.